Consensus for Radiotherapy in Hepatocellular Carcinoma from The 5th Asia-Pacific Primary Liver Cancer Expert Meeting (APPLE 2014): Current Practice and Future Clinical Trials - Park, Hee Chul (Liver Cancer, 2016)
A consensus meeting to develop practice guidelines and to recommend future clinical trials for radiation therapy (RT), including external beam RT (EBRT), and selective internal RT (SIRT) in hepatocellular carcinoma (HCC) was held at the 5th annual meeting of the Asia-Pacific Primary Liver Cancer Expert consortium. Although there is no randomized phase III trial evidence, the efficacy and safety of RT in HCC has been shown by prospective and retrospective studies using modern RT techniques. Based on these results, the committee came to a consensus on the utility and efficacy of RT in the management of HCC according to each disease stage as follows: in early and intermediate stage HCC, if standard treatment is not compatible, RT, including EBRT and SIRT can be considered. In locally advanced stage HCC, combined EBRT with transarterial chemoembolization or hepatic arterial infusion chemotherapy, and SIRT can be considered. In terminal stage HCC, EBRT can be considered for palliation of symptoms and reduction of morbidity caused by the primary tumor or its metastases. Despite the currently reported benefits of RT in HCC, the committee agreed that there is a compelling need for large prospective studies, including randomized phase III trial evidence evaluating the role of RT. Specifically studies evaluating the efficacy and safety of sequential combination of EBRT and SIRT are strongly recommended.